The Effect of Comparative Differences in Composition of Oil Palm Empty Fruit Bunches (OP-EFB) and HDPE Plastics : Physical and Mechanical Properties of Wood Plastic Composite (WPCs) - Yaswan, Rendri; Kasim, Anwar; Nazir, Novizar; Malrianti, Yefsi; Ilyas, R.A (Green Engineering Society, 2025)
Wood Plastic Composite (WPCs) in this study is made from oil palm empty bunches (OP-EFB) which function as fillers and plastics that function as a matrix. This study aims to analyze the effect of the comparison of the composition of the empty fruit bunches of oil palm and HDPE plastic based on the physical and mechanical properties of WPCs. Comparison of the composition of OP-EFB and plastics used in this study were (60:40, 55:45, 50:50, 45:55, 40:60) with the addition of maleic anhydride (MAH) coupling agents and benzoyl peroxide (BPO) initiators. The board manufacturing process is carried out at a temperature of 170oC by pressing for 10 minutes. The results showed that the difference in the ratio of OP-EFB composition and HDPE plastic had a significant effect on the WPCs produced. The optimum ratio of OP-EFB fibers and HDPE plastics is the ratio of 45:55 with the density, water absorption, fracture strength (MOR), parallel surface compressive strength, surface perpendicular compression strength of 0.83 g / cm³, 0.21%, 180.86 kg / cm², 200.48 kg / cm², 47.13 kg / cm². The overall physical and mechanical properties of the WPC are in accordance with SNI 8154-2015 standards regarding wood-plastic composites.